Mixed method study of workforce turnover and evidence-based treatment implementation in community behavioral health care settings. (April 2020) - Herschell, Amy D.; Kolko, David J.; Hart, Jonathan A.; Brabson, Laurel A.; Gavin, James G.
Abstract: Background: Practitioner turnover in behavioral health settings is high and hinders the implementation of new interventions. Objective: This study examined practitioner and organizational characteristics that contribute to high staff turnover in community behavioral health settings. Participants and setting: Clinicians in nine community-based agencies participated. Included agencies treated a high volume of families referred from child welfare. Methods: This study was part of a larger trial testing the effectiveness of a Cognitive Behavior Therapy for family conflict. Authors assessed predictors of turnover quantitatively and qualitatively. Quantitative data was collected prospectively (n = 169) on practitioner and organizational-level variables (e.g., demographics, professional practice, job satisfaction, emotional exhaustion, organizational commitment). Semi-structured interviews with practitioners who left their agencies (n = 40) provided qualitative data retrospectively. Results: Forth-five percent of practitioners left their agencies over three years. Two predictors of final survival status (lower age and lower job satisfaction) were associated with leaving the agency at the p  < .05 level; however, they accounted for very little variance. Qualitative themes highlighted the importance of job characteristics, compensation, productivity requirements, advancement opportunities, and co-worker relationships as influential in the decision to leave. Conclusions: This study highlights the value of a mixed-method approach given that themes emerged from the qualitative interviews that were not accounted for in the quantitative results. Additional research is needed to better understand workforce turnover so that strategies can be developed to stabilize the behavioral health workforce.